Eurasianism: From Ideology to Political and Economic Integration - Suat, B. (Journal of Oriental Studies, 2021)
Euarasianism is the consequence of an intellectual thought that goes back to the 18th century. Eurasianism, which is used in a variety of meanings both geographically and conceptually, is generally examined in two periods. As a continuation of the Slavophile movement, the first period seen at the beginning of the 20th century under the leadership of N. S. Trubetskoy, Petr Savitski and George Vernadski, is called the Classical Eurasianism period. The second period, defined as Neo-Eurasianism, started at the end of the 20th century under the guidance of Alexander Dugin in the light of bridging thoughts of Lev Gumilev who is also considered among the Classical Eurasianists. Eurasianism, which emerged as an anti-Westernization movement on an intellectual basis, was set as a new power center with its political and economic dimensions, after the dissolution of the Soviet Union. In this connection, one of the most important integration project initiated by Moscow after the Commonwealth of Independent States (CIS) is undoubtedly the Eurasian Economic Union. In this study, the impact of Eurasianism on today’s regional integration efforts will be discussed in the context of its ideological, political and economic dimensions. Key words: Eurasia, Eurasianism, Eurasian Economic Union, Integration, Russia,